Systems Neuroscience and Rehabilitation - Kansaku, Kenji; Cohen, Leonardo G.; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2011)
Rapidly growing knowledge in systems neuroscience may contribute to expand the range of activities in persons with disabilities, but in its practical application, cooperation between experts in different research fields is necessary. In this conference, the guest speakers and audiences will be from wide range of research fields; e.g., systems-neuroscience, neurology, engineering, psychology, and the attendees will discuss the possibilities.
Keywords: Medicine; Medicine & Public Health; Medicine/Public Health, general